Psychopharmacology and ethnicity: A comparative study on Senegalese and Italian men. (20th April 2020) - Marazziti, Donatella; Stahl, Stephen M.; Simoncini, Marly; Baroni, Stefano; Mucci, Federico; Palego, Lionella; Betti, Laura; Massimetti, Gabriele; Giannaccini, Gino; Dell'Osso, Liliana
Abstract: Objectives: Ethnicity represents a crucial factor in influencing response to psychotropic drugs. Some data indicate that functional polymorphisms of two candidate genes of the serotonin (5-HT) transporter (SERT) may affect the response to selective 5-HT reuptake inhibitors (SSRIs). The present study aimed to compare the platelet SERT, through the specific [ 3 H]paroxetine ([ 3 H]Par) binding, and plasma oxytocin (OT) levels in 20 Senegalese and in 20 Italian men. Methods: No subjects had family or personal history of any major psychiatric disorder, or had ever regularly taken psychotropic drugs, or were suffering from any physical illness. Results: Senegalese men showed statistically significant higher density ( B max, fmol/mg protein, mean ± SD) of [ 3 H]Par binding sites (2105.00 ± 473.15 vs 1139.85 ± 213.58, P < 0.001), as well as more elevated plasma OT levels (pg/ml, mean ± SD) (OT: 18.08 ± 4.46 vs 6.62 ± 2.91) than Italian men. Conclusions: These differences, possibly due to genetic or dietary reasons, or even to gender, might affect the response to psychopharmacological compounds. Our findings would suggest specific caution when administering psychotropic compounds to non-European individuals, and the need of further studies in this emerging field of neuropsychopharmacology.